2019
DOI: 10.1039/c9dt02824b
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnO thin films obtained from molecular layer deposited “zincones”

Abstract: The synthesis of MLD-derived mesoporous ZnO with 20% of porosity is demonstrated and studied by advanced in situ characterization techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…The MLD process included the following four steps, repeated for each cycle: (1) DEZ dose, (2) Ar purging, (3) EG dose, and (4) Ar purging. To ensure the saturation behavior of the four steps as previously investigated [ 36 ], the deposition recipe was fixed to 0.15 s for the DEZ dose, 60 s for the first Ar purge, 0.2 s for the EG exposure, and 170 s for the second Ar purge. The 16 sccm set for the Ar flow resulted in working pressure of 0.15 torr, and relative precursor pressures of Δp = (0.2 ± 0.02) torr for DEZ and of Δp = (0.1 ± 0.02) torr for EG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLD process included the following four steps, repeated for each cycle: (1) DEZ dose, (2) Ar purging, (3) EG dose, and (4) Ar purging. To ensure the saturation behavior of the four steps as previously investigated [ 36 ], the deposition recipe was fixed to 0.15 s for the DEZ dose, 60 s for the first Ar purge, 0.2 s for the EG exposure, and 170 s for the second Ar purge. The 16 sccm set for the Ar flow resulted in working pressure of 0.15 torr, and relative precursor pressures of Δp = (0.2 ± 0.02) torr for DEZ and of Δp = (0.1 ± 0.02) torr for EG.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work from our group [ 35 ] showed that zincone-like thin films can be deposited via sub-saturated plasma-enhanced atomic layer deposition and that porous ZnO can be obtained from them via calcination, albeit the porosity achieved was quite low (1–5%). More promising porosity values were reached in the following publication [ 36 ], in which the zincone thin films were deposited via MLD using diethyl zinc (DEZ) and ethylene glycol (EG) as the metal and organic precursor, respectively. Subsequent calcination at 400 °C led to an open porosity of approximately 19% in the obtained ZnO thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Diethylzinc is the most common precursor for zinc in the ALD/MLD processes; it is often combined with HQ, [54,55,66,107,133,230,[244][245][246][247]250,361,366,[370][371][372][373][374][375][376][377][378] but also with many other organic components. [46,48,115,134,211,212,226,228,233,238,239,241,265,272,278,324,345,349,[379][380][381][382][383][384][385][386][387][388]…”
Section: Aluminum- Zinc- and Titanium-based Processesmentioning
confidence: 99%
“…Diethylzinc is the most common precursor for zinc in the ALD/MLD processes; it is often combined with HQ, [ 54,55,66,107,133,230,244–247,250,361,366,370–378 ] but also with many other organic components. [ 46,48,115,134,211,212,226,228,233,238, 239,241,265,272,278,324,345,349,379–390 ] The DEZ + HQ process has been widely utilized for the growth of different superlattice structures in which the Zn–HQ layers are combined with thicker ZnO layers grown with ALD cycles from DEZ plus H 2 O. Another zinc precursor employed in ALD/MLD is zinc acetate.…”
Section: Brief Account Of Ald/mld Processes Developedmentioning
confidence: 99%
“…Once the alucone film was irreversibly saturated with Li atoms, it became electronically conductive. Thirdly, MLD hybrid films (e.g., zincone, magnesicone) have been converted to corresponding highly porous metal oxide materials (e.g., ZnO, MgO) by removing the organic backbones via post-annealing (Perrotta et al, 2019a;Perrotta et al, 2019b;Kint et al, 2020). These porous metal oxide structures might be used reactive barrier layers or porous substrates for Li-ion composite solid electrolytes.…”
Section: Other New Mld Thin Films Promising For Rechargeable Batteriesmentioning
confidence: 99%